Control system - WATANABE TADASHI (2024)
Provided is support information for more easily determining the state of a control object. The control system collects an image obtained by imaging a subject in association with an imaging time, periodically collects a state value of the subject, and acquires, for each time of a predetermined length, a representative value of the state value collected during the time. The control system arranges and displays a time waveform of a state value collected within the time corresponding to the representative value, and a moving image of an image associated with an imaging time corresponding to the time, for the representative value selected from among the acquired representative values for each time by a user operation. 提供用于更容易地判断控制对象的状态的支持信息。控制系统将拍摄对象所得的图像与拍摄时间相关联地收集，周期性地收集对象的状态值，按照每个预先确定的长度的时间取得在该时间内收集的状态值的代表值。控制系统针对通过用户操作从所取得的每个时间的代表值中选择出的代表值，排列显示在与该代表值对应的上述时间内收集到的状态值的时间波形、以及与符合该时间的拍摄时间关联的图像的动态图像。